Lightwave control of topological properties in 2D materials for sub-cycle and non-resonant valley manipulation - Jimenez-Galan, Alvaro; Silva, R. E. F.; Smirnova, Olga; Ivanov, Mikhail (Misha) (Nature Photonics, 2020)
Modern light generation technology offers extraordinary capabilities for sculpting light pulses, with full control over individual electric field oscillations within each laser cycle1–3. These capabilities are at the core of lightwave electronics—the dream of ultrafast lightwave control over electron dynamics in solids on a sub-cycle timescale, aiming at information processing at petahertz rates4–8. Here, bringing the frequency-domain concept of topological Floquet systems9,10 to the few-femtosecond time domain, we develop a theoretical method that can be implemented with existing technology, to control the topological properties of two-dimensional materials on few-femtosecond timescales by controlling the sub-cycle structure of non-resonant driving fields. We use this method to propose an all-optical, non-element-specific technique, physically transparent in real space, to coherently write, manipulate and read selective valley excitation using fields carried in a wide range of frequencies and on timescales that are orders of magnitude shorter than the valley lifetime, crucial for the implementation of valleytronic devices11,12.
CRIS-Team Scopus Importer:2023-04-20